A Spontaneous Pneumomediastinum During an Asthma Exacerbation - Joseph Derry; Harshana Bandara (Respirology Case Reports)
ABSTRACT This case highlights the rare possibility of having pneumomediastinum in patients with asthma without having other structural lung disease. This also highlights the importance of vigilant reading of the chest x‐ray, including the proper inspection of the soft tissues areas.